Online public relations: What are the mechanisms that should be used by practitioners to elevate their performance? - Rasha Adel (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2020)
Despite the elevated interest in new technologies in the public relations practice, their use is still achieved in a random, traditional, disorganized way and without a particular strategy or methodology. This randomness in non-use may be caused by the lack of conviction of the role of modern technological tools and their importance to activate the dialogue between the organization and its audience. In addition to enabling them to achieve their objects such as promotion, building a strong reputation and increase loyalty and thus increase sales or services provided. The other reason is that this area is still considered relatively new. Literature still lacks studies that show the mechanisms that practitioners should follow to improve and develop their performance, although many studies have shown that there are many gaps and issues in the online PR practice, such as weaknesses in technological skills, weakness in the concept of online pr. Studies have also found factors that affect on the non-use of these tools or use them in an abusive manner. Therefore, there is a need for studies to show the mechanisms of dealing with these tools effectively. This study attempted to explore the literature in this field and found several mechanisms that could be used to improve and develop the practice of online PR.